2018
DOI: 10.1007/s00705-018-3744-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of a luminescence syncytium induction assay (LuSIA) for easily detecting and quantitatively measuring bovine leukemia virus infection

Abstract: Bovine leukemia virus (BLV) causes enzootic bovine leukosis and is closely related to the human T cell leukemia virus. Since BLV infection mostly occurs via cell-to-cell transmission, BLV infectivity is generally measured by culturing BLV-infected cells with reporter cells that form syncytia upon BLV infection. However, this method is time-consuming and requires skill. To visualize the infectivity of BLV, we developed a new assay called the luminescence syncytium induction assay (LuSIA) that is based on a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…Previous studies have demonstrated that the proviral load, which represents the BLV genome integrated into the host genome, is an important index for estimating the BLV infection stage. Proviral load is associated with disease progression [37,38,39], lymphocyte count [40], viral biokinetics [41], viral infectivity [42], and virus shedding into the saliva and nasal secretions [43]. Among the cows with high risk for BLV transmission, the cows in which BLV provirus was detected in the nasal secretion and saliva had a proviral load of over 14,000 copies/10 5 cells and 18,000 copies/10 5 cells in their blood sample, respectively [43].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the proviral load, which represents the BLV genome integrated into the host genome, is an important index for estimating the BLV infection stage. Proviral load is associated with disease progression [37,38,39], lymphocyte count [40], viral biokinetics [41], viral infectivity [42], and virus shedding into the saliva and nasal secretions [43]. Among the cows with high risk for BLV transmission, the cows in which BLV provirus was detected in the nasal secretion and saliva had a proviral load of over 14,000 copies/10 5 cells and 18,000 copies/10 5 cells in their blood sample, respectively [43].…”
Section: Introductionmentioning
confidence: 99%
“…BLV proviral load (PVL), which represents the retroviral genome integrated into the host genome ( 5 , 6 ), correlates strongly with not only BLV infection capacity as assessed by syncytium formation ( 7 , 8 ), but also EBL progression ( 7 , 9 , 10 ). Additionally, it is a useful index for estimating transmission risk ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional syncytia formation assay was performed as described previously [33]. Transfected CC81 cells were fixed using May-Grunwald solution (Merck, Darmstadt, Germany) for 2 min and then stained with May-Grunwald solution diluted with phosphate buffer for 3 min and with diluted Giemsa solution (Sigma-Aldrich) for 15 min.…”
Section: Syncytia Formation Assaymentioning
confidence: 99%